Risco sanitário associado ás importações de equídeos realizados pelo Brasil de 2010-2015 - Thiago Luiz Mendes Arcebispo (2016)
The importation of equids by Brazil constitutes an important source of genetic diversity and breeds improvement. However the risk of spreading diseases is inherently associated to the international transit of any animal species. In front of this, this study aims to assess the equids importations done by Brazil from 2010 to 2015, identifying and dimensioning the sanitary risks from this activity. Data from three different institutions were correlated for this purpose: from the Ministry of Development, Industry and International Trade (MDIC); from the World Organization for Animal Health (OIE); and from the Ministry of Agriculture, Livestock and Food Supply (MAPA). In the study period 7845 importations of equids were made by Brazil from 27 different countries, and admitted through 11 ports. This scenario was submitted to net analysis which allowed the identification of three diseases as major hazards for their vast presence in the equids origins, the diseases were: Equine Infectious Anemia (EIA); Equine Viral Arteritis (EVA); and Contagious Equine Metritis (CEM). We verified that a high percentage of the importations comes from countries with presence or infestation of the analyzed diseases (EIA 40.2%; EAV 78.4%; CEM 38.6%) and that in despite of the fact that the official veterinary service makes the adequate requirements of negative tests for the diseases reported by the origin countries, the risk of introducing carriersincreases as we consider the prevalence of the diseases in imported equids and the sensitivity of the of the diagnostic tests demanded. Proceeding to a Deterministic Risk Assessment, as proposed by OIE, we estimated the average number of equids infected that entered the Brazil was:17 for EIA; 9 for EAV; and 22 for CEM. The probability of introduction of at least one infected animal during the period was superior to 99.99% to all three diseases.